2006
DOI: 10.1088/0022-3727/39/13/035
|View full text |Cite
|
Sign up to set email alerts
|

Coil impedance variation due to induced current at the edge of a conductive plate

Abstract: The time-harmonic induced current in a conductive plate has been calculated for an excitation by a normal coil near the plate edge. Using series expansions in elementary functions, the quasi-static solution for the plate is matched to the solution for the region outside the plate to ensure continuity of the tangential magnetic field and the normal magnetic flux density at the air–conductor interface. The continuity of the field is achieved by mode matching in a truncated domain. Predictions of the coil impedan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 8 publications
(19 reference statements)
0
21
0
1
Order By: Relevance
“…For reference, the following expressions for the electromagnetic field are given. Firstly, the magnetic field is expressed as (4) and the components of the magnetic field are therefore (5) (6) and (7) The electric field in source-free regions is given by (8) and its components are therefore (9) (10) and (11) By using a scalar decomposition with as the preferred direction, Fig. 2, and selecting the truncation boundary condition judiciously we have avoided coupling of the TE and TM modes at the surface.…”
Section: B Scalar Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…For reference, the following expressions for the electromagnetic field are given. Firstly, the magnetic field is expressed as (4) and the components of the magnetic field are therefore (5) (6) and (7) The electric field in source-free regions is given by (8) and its components are therefore (9) (10) and (11) By using a scalar decomposition with as the preferred direction, Fig. 2, and selecting the truncation boundary condition judiciously we have avoided coupling of the TE and TM modes at the surface.…”
Section: B Scalar Decompositionmentioning
confidence: 99%
“…The dedicated wedge kernel has been used to compute the eddy current probe signals due to cracks in the region of the edge. We apply the domain truncation approach used previously to compute the field of a coil in the presence of a homogeneous right-angled wedge [9], [10] and at the edge of a homogeneous plate [11]. Truncation of the problem domain and the imposition of additional boundary conditions has the effect of imposing a periodic solution that approximates the corresponding unbounded domain field.…”
Section: Introductionmentioning
confidence: 99%
“…Driver-pickup eddy current non-destructive testing is a wellestablished method for the inspection of metallic objects [1]. It is relatively inexpensive, fast and reliable in comparison with other inspection technologies.…”
Section: Introductionmentioning
confidence: 99%
“…In transient eddy current experiments, for instance, agreement with experimental data is limited to later times when feedback effects become less prominent [11]. In other cases, authors often assume non-magnetic samples for experimental validation [1][2][3][4], constrained sample geometries [11], and resort to fitted parameters [3] or convenient smoothing functions [9]. In some instances [9][10][11][12][13], analytical models have been presented with limited or no experimental support.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, if one is interested in detecting smaller cracks, it is necessary to use higher frequencies. The higher sensitivity for detecting corner cracks is largely due to the confinement of the eddy currents by the edge of the sample as predicted by Theodoulidis and Bowler [4,5]. When a POD was performed on in-service material it was found that while the a90/95 for the mid-bore cracks hardly changed, that of the corner cracks grew substantially from 0.29 mm to 0.82 mm [6].…”
Section: Introductionmentioning
confidence: 76%